1+sec2A/tan2A=cotA
prove that
Attachments:
![](https://hi-static.z-dn.net/files/d61/90d60188f5f6b1364f2ee0708fce5d86.jpg)
jaywantvichare8014:
plz give me ans
Answers
Answered by
6
(1+sec2A)/(tan2A)
= (1/tan2A) + (sec2A/tan2A)
= cot2A + csc2A
= [(cot^2 (A) - 1) / 2cotA] + [(1+tan^2 (A)) / 2tanA]
= [tanA (cot^2 (A) - 1) + cotA (1+tan^2 (A))] / (2 tanA cotA)
= [cotA - tanA + cotA + tanA] / 2
= 2 cotA / 2
= cotA.....hope this helps u..
= (1/tan2A) + (sec2A/tan2A)
= cot2A + csc2A
= [(cot^2 (A) - 1) / 2cotA] + [(1+tan^2 (A)) / 2tanA]
= [tanA (cot^2 (A) - 1) + cotA (1+tan^2 (A))] / (2 tanA cotA)
= [cotA - tanA + cotA + tanA] / 2
= 2 cotA / 2
= cotA.....hope this helps u..
Similar questions